2021
DOI: 10.1186/s12889-020-10144-2
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting and doing the same: school nurses’ descriptions of promoting participation in health visits with children of foreign origin

Abstract: Background School nurses in the school health services are assigned to promote health and participation among children when conducting health visits. Still, for children of foreign origin this promotion of participation might be hampered by challenges related to cultural diversity and language barriers. Therefore, knowledge needs to be developed regarding how these children’s participation can be promoted, to support them in sharing and describing matters important for their health. The aim was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…School nurses might thereby use their previous knowledge and experience, which is considered important in guiding and assuring good quality in clinical practice [ 48 , 49 ]. In addition, using approaches that adjust to the child’s needs, language proficiency and cultural or national background when encountering children who have migrated or whose parents have migrated is described as common among school nurses [ 50 ]. The possibility of adjustment is especially important for children who have migrated or whose parents have migrated as experiences, living conditions and health differ greatly within this group of children [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…School nurses might thereby use their previous knowledge and experience, which is considered important in guiding and assuring good quality in clinical practice [ 48 , 49 ]. In addition, using approaches that adjust to the child’s needs, language proficiency and cultural or national background when encountering children who have migrated or whose parents have migrated is described as common among school nurses [ 50 ]. The possibility of adjustment is especially important for children who have migrated or whose parents have migrated as experiences, living conditions and health differ greatly within this group of children [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wahlström et al (2021) have shown that school nurses describe using a combination of approaches when promoting the participation of children of foreign origin in health visits. This combination included adjustments made based on both the children's language proficiency and cultural or national background and the needs and wishes of the individual child as well as doing the same for all children.…”
Section: Practical Implications and Recommendations For Further Researchmentioning
confidence: 99%
“…School nurses encountering unaccompanied refugee children describe the encounters as being hampered by their lack of knowledge about trauma‐informed care and intercultural nursing and highlight a need of school nurses having self‐awareness (Musliu et al., 2019 ). In addition, research shows how school nurses adjust their approach in encounters with children with migration experiences (Wahlström et al., 2021 ), but research from the children's perspective is lacking. Overall, research on healthcare encounters from the perspective of children with migration experiences is scarce (Curtis et al., 2018 ; Spencer et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have been conducted studying preschool teachers', teachers', school nurses', school social workers' and school psychologists' encounters with children, and have highlighted culture as relevant, especially in encounters with children who have migrated [15][16][17][18][19][20] and in relation to race or ethnicity. 21 Yet there is a lack of reviews collating research regarding school health professionals' (ie, school nurses, school social workers, school doctors and school psychologists) understanding of culture.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%